Ureasil-Polyether-CoFe2O4Nanocomposites: Coupling a Drug Delivery System and Magnetic Hyperthermia - De Santana, Willian Max O. S. [UNESP]; Abramson, Sébastien; Fini, Rodolfo [UNESP]; Caetano, Bruno L. [UNESP]; Ménager, Christine; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (American Chemical Society (ACS), 2021)
In this work, we evaluate the effect of the ureasil-polyether hybrid nature on the magnetic hyperthermia (MH) properties and drug delivery patterns of nanocomposites prepared by the conjugation of cobalt ferrite (CoFe2O4) superparamagnetic nanoparticles (SPN) with ureasil-poly(propylene oxide) (UPPO) and ureasil-poly(ethylene oxide) (UPEO). The results of small-angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC) analyses evidenced that the nanoscopic structure and thermal properties remained essentially unaffected by conjugation of the SPN with the hybrid material. The lower heat capacity of the UPPO-CoFe2O4 nanocomposite promoted a higher efficiency of MH compared to the UPEO-CoFe2O4 nanocomposite. The temperature variations achieved by UPPO-CoFe2O4 and UPEO-CoFe2O4 were 34 and 20 °C, respectively, when subjected to an alternating magnetic field (AMF) for 240 s. The drug delivery patterns of sodium diclofenac (SDCF) from UPPO and UPEO were unaffected by the conjugation with SPN or by MH.
Keywords: cobalt ferrite; magnetic hyperthermia; nanocomposites; organic-inorganic hybrid materials; siloxane-polyether